Transformasi Manajemen Sekolah Melalui Kurikulum Merdeka Di Kabupaten Musi Rawas - Kartika; Somantri , Manap; Putri Kartiwi, Asti (UNIVERSITAS BENGKULU, 2025)
This study aims to describe the implementation of Merdeka Curriculum in the transformation of school management. This research approach is descriptive quantitative with a survey method. The subjects of this study were principals and teachers in Musi Rawas Regency. The data collection technique was a questionnaire in the form of a Google form. The result of this study is that in the implementation of Merdeka Curriculum, school management transformation occurs, which includes curriculum and learning management transformation, learner management transformation, educator and education personnel management transformation, facilities and infrastructure management transformation, and school environment management transformation, which varies according to the indicators of each dimension.